تقييم كفاءات الطلاب: بين الواقع والتحديات - طباع, فاروق (جامعة الوادي University of Eloued, 2017)
يعتبر تقييم الكفاءات من المواضيع التي لقيت اهتماما متزايدا خلال العقدين الأخيرين، وقد اتجهت الممارسات التربوية الحديثة نحو تقييم الكفاءات بدلا من تقييم المعارف المنعزلة، واستخدام وضعيات مركبة بدلا من بنود ذات محتويات مجردة من السياق. يهدف المقال الحالي إلى مناقشة مسألة تقييم الكفاءات من خلال توضيح مفهوم الكفاءة ومبررات الانتقال من التقييم الموضوعي إلى تقييم الكفاءات، ومقارنة تقييم الكفاءات بتقييم الأداء، وتوضيح تقييم كفاءات الطلاب وصعوباته من ناحية الممارسات التربوية. For two latter decades, researchers and specialists in educational field interested about competences assessment issue. From his appearance in reaction to traditional practices accrue exhaustive changes to assess students’ acquisitions. In first, educational practices focused on isolated and abstract content of knowledge and skills assessment using multiple choices, true-false and short answer questions. Hereafter, the practices oriented toward using alternative procedures to competences’ assessment based on complex tasks with open-ended problems, essays, exhibitions, experiments, projects and Portfolios. However, competences assessment as a complex issue need to be clarified through identifying the concept of competence, presenting the reasons of path from objectives to competences assessment, identifying them comparing with performance assessment, and difficulties of competences assessment from the perspective of educational practices.
مقال
Keywords: الكفاءة؛ تقييم الكفاءات؛ تقييم الأداء؛ الوضعيات المركبة; competence; competences assessment; performance assessment; complex situation